PENGARUH LIMPASAN PERMUKAAN TERHADAP SISTEM DRAINASE DI KECAMATAN KEFAMENANU KABUPATEN TIMOR TENGAH UTARA - Suhudi Suhudi; Sebastianus Seran (Universitas Tribhuwana Tunggadewi, 2015)
Drainage system is the exile of overload water by flowing through surface drainage or sub surface drainage. The overload of water is rain drop. Based on the condition, the run off surface which caused the overload water should be handled by planning the drainage well and supported. It was made for smoothing the water acces so that it won’t be blocked by the rubbish also anticipate the scrape of soil.The research was held at Kelurahan Benpasi Kecamatan Kefamananu Kabupaten TTU from January until March, 2015. It used the rational method, it was Qa = 0,278.C.I.A.The primary data were the condition of the run off surface and the existing channel. The secondary data, such as: the population report, rain, the map of field arrangement and topography map. The result of analysis stated that the number of rain during 10 year in amount of 92,918mm with the flood discharge in amount of 3,52mᶟ/second. The biggest capacity of existing channel was Q4 = 0,231 mᶟ/second. The planned construction design was made of the river stone couple which has square shape in size b = 1,30m and h = 0,69m on channel 4. The plannedchannel capacity in amount of 3,64mᶟ/second